Application of Healthy and Safe Internet in Controlling Negative Internet Impacts for Students at MI Darussa'adah, South Jakarta. - Heri Satria Setiawan; Rudi Hermawan; Rudi Apriyadi Raharjo (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
The use of gadgets today has become a major requirement for everyone. In the present, many children are using gadget since childhood especially to watch videos on youtube, play online games, and search for learning materials through the help of the internet.This can be a good step so that children easily adapt to technological developments. But on the other hand, parents must worry if children play gadgets too often and access things that are not age-appropriate, which is not necessarily suitable for their age. It is important for parents to monitor the use of gadgets in children. The role of parents and teachers in dealing with this situation, they must have the ability to monitor and control the use of the internet by parental control applications. It is able to select, limit, and supervise what applications can be accessed by children and adolescents so they can still use gadgets as a learning and entertainment medium without having to be addicted and poisoned by negative content.